Twisters : the real story [videorecording (DVD)] - Inness, Peter; Knightley, Paul; Botten, Paul; Cline, Rich (Reel2Reel Films Ltd., 2024)
In 1996, the film "Twisters" was released, a riveting film about tornado researchers. Now, this captivating documentary brings viewers closer than ever before to the pulse-pounding reality of storm chasing, exploring the unwavering motivations that drive these courageous individuals to the very edge of danger in pursuit of understanding the fury of nature's most deadly phenomenon.